1995
DOI: 10.1002/food.19950390103
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed meal‐Glucosinolates and their antinutritional effects Part 6. Taint in end‐products

Abstract: From the present review it is clear that glucosinolates and their breakdown products may pass in small amounts into such products as meat, milk or eggs without noticeable deterioration in their taste. When applying low glucosinolate rapeseed meal (LG-RSM) as the sole high protein component of concentrate mixture for cows, the level of rapeseed glucosinolates breakdown products should not exceed 0.1 mumol/l oxazolidinethione, 10 mumol/l unsaturated nitriles and 100 mumol/l thiocyanate. At these levels no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 68 publications
0
18
0
3
Order By: Relevance
“…As demonstrated by Mawson et al (1995), Ahmad et al (2007), and Mushtaq et al (2007), diets containing up to 200 g/kg of low-glucosinolate RSM had no adverse effects on carcass and breast meat yields and meat quality in broiler chickens. Similar muscle yields were observed in the current study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As demonstrated by Mawson et al (1995), Ahmad et al (2007), and Mushtaq et al (2007), diets containing up to 200 g/kg of low-glucosinolate RSM had no adverse effects on carcass and breast meat yields and meat quality in broiler chickens. Similar muscle yields were observed in the current study.…”
Section: Discussionmentioning
confidence: 83%
“…The use of rapeseed meal (RSM) derived from double zero, low-glucosinolate, and low-erucic acid varieties of rapeseed in monogastric animal nutrition is limited due to the low available energy content and the presence of antinutritional factors, including glucosinolates, sinapine, and phytate (Mawson et al, 1995), and dietary fiber components, such as tannins or nonstarch polysaccharides (NSP; Slominski and Campbell, 1990;Kocher et al, 2000). It has been demonstrated that dietary fiber components may reduce protein and energy digestibilities in diets containing high levels of RSM (Slominski, 1997;Chibowska et al, 2000;Kocher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Following introduction and popularization of low glucosinolate rapeseeds numerous doubts arose concerning the suitability of traditional processing technology adjusted for the processing of rapeseeds of almost tenfold lower glucosinolate content. The greatest doubts concern excessive temperature and time to which desolventized meal is exposed during toasting (90-120 "C, 35 -40 min) necessary for glucosinolate degradation and partial removal of their breakdown products [29,38,44]. The same is true for the conditioning of rapeseeds prior to oil extraction the aim of which is, among others, to inactive native enzymes including myrosinase [29, 411. During that process flaked rapeseeds are gradually heated for a long time (70-105 "C, 45 min) [28] which favours glucosinolates breakdown due to their contact with myrosinase as a result of destruction of the seeds cell structure.…”
Section: Traditional Technology and Its Modificationsmentioning
confidence: 99%
“…Glucosinolates, and chiefly their breakdown products, are the most significant factors impairing the nutritional quality of rapeseeds and post-extraction meal. Chemical characteristics of these compounds [33] and complex mechanism of their antinutritional influence on the animal organism were described in the earlier parts of this paper in which the effect of glucosinolates on flavour and palatability [34], animal growth and performance [35], goitrogenicity and internal organs abnormalities in animal [36], animal reproduction [37] and taint in end products [38] were also discussed. The present paper, the last of the series, presents current technological achievements in quality improvement of protein products obtained from rapeseeds especially of low glucosinolate content.…”
Section: Introductionmentioning
confidence: 99%
“…2 Alguns estudos mencionam efeitos nocivos dos glicosinolatos na saúde: a formação de bócio, 3 características antinutricionais e toxicidade causadas pela dieta, 4 efeitos citotóxicos e a indução de aberrações cromossomiais constam da literatura. [5][6][7][8] Existe, no entanto, uma dicotomia no que tange os efeitos de glicosinolatos e isotiocianatos na dieta diária.…”
Section: Introductionunclassified